Potential use of some plant extracts against foot rot of rice (Oryza sativa L.) - Bhardwaj, Surender Kumar; Laura, Jitender Singh (ORYZA-An International Journal of Rice, 2018)
In continuation of our ongoing efforts to search for plant based eco-friendly bio- protectant against diseases of cereal crops. 32 plants samples of 26 plants species were bio-assayed by measuring the mycelia growth inhibition of Fusarium moniliforme, a causal organism of foot rot of rice. The tested results showed a differential activity of the plant extracts against the mycelium growth. The combined fruit and stem extracts of Terminalia belerica in general showed a strong enhancement in activities over the individual fruit extracts of T. belerica and stem extracts of T. belerica against the mycelium growth. The root extracts of Salvadora persica and petal extracts of Rosa damascena also showed strong inhibitory effect against the tested fungi. The leaf and bark extracts of T. belerica, leaf extract of Tectona grandis, Mimosa hamata and petal extracts of Tagetes erecta showed appreciable good inhibitory effect against the tested fungi.